Audio-Tactile and Peripersonal Space Processing Around the Trunk in Human Parietal and Temporal Cortex: An Intracranial EEG Study. (12th July 2018) - Bernasconi, Fosco; Noel, Jean-Paul; Park, Hyeong Dong; Faivre, Nathan; Seeck, Margitta; Spinelli, Laurent; Schaller, Karl; Blanke, Olaf; Serino, Andrea
Abstract: Interactions with the environment happen within one's peripersonal space (PPS)—the space surrounding the body. Studies in monkeys and humans have highlighted a multisensory distributed cortical network representing the PPS. However, knowledge about the temporal dynamics of PPS processing around the trunk is lacking. Here, we recorded intracranial electroencephalography (iEEG) in humans while administering tactile stimulation (T), approaching auditory stimuli (A), and the 2 combined (AT). To map PPS, tactile stimulation was delivered when the sound was far, intermediate, or close to the body. The 19% of the electrodes showed AT multisensory integration. Among those, 30% showed a PPS effect, a modulation of the response as a function of the distance between the sound and body. AT multisensory integration and PPS effects had similar spatiotemporal characteristics, with an early response (~50 ms) in the insular cortex, and later responses (~200 ms) in precentral and postcentral gyri. Superior temporal cortex showed a different response pattern with AT multisensory integration at ~100 ms without a PPS effect. These results, represent the first iEEG delineation of PPS processing in humans and show that PPS and multisensory integration happen at similar neural sites and time periods, suggesting that PPS representation is based on a spatial modulation of multisensory integration.